2018
DOI: 10.1177/1403494817744119
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a web-based national child health-care programme in a local context: A complex facilitator role

Abstract: Facilitating a national guideline or decision support in a local context is a complex task that requires an advocating and mediating role. For successful implementation, guidelines and decision support, such as a web-based guide and the new child health-care programme, must match professional consensus and needs and be seen as relevant by all. Participation in the development and a strong bottom-up approach was important, making the web-based guide and the programme relevant to whom it is intended to serve, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…The result showed that the national CHC program is still not implemented in all county councils/regions, and the use of RHB varied. This was also found in earlier studies of Swedish CHC and RHB 15,16,19 and contradicts the intention to offer an equal CHC contributing to equality in child health. 14 An overall category of understanding was RHB as a contributing determinant to an equal CHC and national equivalence.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The result showed that the national CHC program is still not implemented in all county councils/regions, and the use of RHB varied. This was also found in earlier studies of Swedish CHC and RHB 15,16,19 and contradicts the intention to offer an equal CHC contributing to equality in child health. 14 An overall category of understanding was RHB as a contributing determinant to an equal CHC and national equivalence.…”
Section: Discussionmentioning
confidence: 57%
“…Tell et al 15 found the ambivalence of CHC coordinators regarding parts in the new CHC program and to discontinuing use of their local guidelines in favor of RHB. As the MCHCUs have shown to be the most commonly used source of knowledge and methodological guidance for CHC nurses' work 19 and are important facilitators in the implementation of RHB, 15 these are dilemmas that people need to struggle with in county councils/regions. According to Wallby, 17 varied interventions are needed to get an equitable CHC, but they must not be at the expense of universal efforts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations